2017
DOI: 10.15406/frcij.2017.04.00104
|View full text |Cite
|
Sign up to set email alerts
|

Methods of Skeletal Age Estimation used by Forensic Anthropologists in Adults: A Review

Abstract: Reconstruction of biological profile of unknown individuals would be incomplete without age determination. Forensic anthropologists use skeletal indicators involved in processes of bone resorption, deposition and remodelling which are time-related to estimate age of the individual. Estimating age in adults remains a challenging task to the forensic anthropologists because of the complexity and individual variations seen in the aging process and the gamut of environmental factors influencing the same. Age provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 33 publications
0
22
0
1
Order By: Relevance
“…Age at death was estimated using skull sutures, pubic symphysis, and auricular surface metamorphosis characteristics (Buikstra & Ubelaker, 1994); all possible age indicators were utilised for each skeleton. In cases of a strong disagreement between methods, the auricular surface metamorphosis was chosen here as an accurate and reliable method for age estimation (Meindl & Lovejoy, 1989;Priya, 2017). Several studies demonstrated that juvenile individuals and adults over 50 years old may reflect a misrepresentative manifestation of muscular development (Al-Oumaoui et al, 2004;Kennedy, 1998;Niinimäki, 2011;Niinimäki & Sotos, 2013;Robb, 1998;Wilczak, 1998a;Zumwalt, 2006).…”
Section: Determination Of Sex and Agementioning
confidence: 99%
“…Age at death was estimated using skull sutures, pubic symphysis, and auricular surface metamorphosis characteristics (Buikstra & Ubelaker, 1994); all possible age indicators were utilised for each skeleton. In cases of a strong disagreement between methods, the auricular surface metamorphosis was chosen here as an accurate and reliable method for age estimation (Meindl & Lovejoy, 1989;Priya, 2017). Several studies demonstrated that juvenile individuals and adults over 50 years old may reflect a misrepresentative manifestation of muscular development (Al-Oumaoui et al, 2004;Kennedy, 1998;Niinimäki, 2011;Niinimäki & Sotos, 2013;Robb, 1998;Wilczak, 1998a;Zumwalt, 2006).…”
Section: Determination Of Sex and Agementioning
confidence: 99%
“…The value of teeth in assessing individual age is widely accepted in forensic sciences and numerous areas of human life, such as socioeconomic, legal aspects, and dental treatment planning (Koshy and Tandon 1998;Franco et al 2013). Several studies have been performed on the estimation of human biological age (Cameriere et al 2004); most of those are focused on skeletal markers (Priya 2017) such as epiphyseal and cranial suture fusions (Ebeye et al 2016), hand-wrist bones (Benjavongkulchai and Pittayapat 2018), sternoclavicular bones (Ufuk et al 2016), and dental maturation (Manjunatha and Soni 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Örneğin, yaş tahmini için kullanılan kemik özellikleri, olgunlaşma süresi ve çevresel faktörlerden etkilenebilir. Bu nedenle, uzamış bir olgunlaşma süresi ve oldukça değişken çevresel faktörlerin bir spektrumu, biyolojik asimetri için daha fazla olasılık sağlayarak iskelet kalıntılarından yapılan yaş tahminlerinin yanlış yorumlanmasına neden olabilir (Priya, 2017). Bu çalışmalardan biri Stoyanova ve arkadaşlarının (2019), 88 modern Amerikalı erkek bireye ait 3B lazer tarama yöntemi ile görüntüledikleri pubik simfizisde asimetri varlığı ve yaş tahminine etkisi hakkında yaptıkları araştırmadır.…”
Section: Discussionunclassified